Healthy Eating: Improving Your Convenience Foods - Emily Minton; Linda B. Bobroff (EDIS, 2016)
Convenience foods are foods that require little preparation. Some convenience foods only require heating and are ready to eat in less than five minutes! The majority of convenience foods are processed foods. However, precut, prewashed, frozen, and canned fruits and vegetables also can be classified as convenience foods. They are healthy foods but are usually more expensive than less prepared fresh fruits and vegetables. This 2-page fact sheet is a major revision that discusses pros and cons of convenience foods, improvement of nutritional quality, common convenience foods and easy additions, and additional tips. Written by Emily Minton and Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, revised March 2016.